Activation of Natural Zeolite and Its Application for Adsorbents in Domestic Wastewater Treatment in Tembalang District, Semarang City - Suhartana Suhartana; Pardoyo Pardoyo (Jurnal Kimia Sains dan Aplikasi, 2020)
Tembalang is one of the districts in the city of Semarang whose economic growth is rapid. There are 12 sub-districts in Tembalang district, one of which is the Tembalang sub-district, which is within the campus area of Diponegoro University. When compared with other sub-district in the Tembalang district, the Tembalang sub-district community's need for clean water and domestic wastewater disposal is very high because of its dense population. Handling domestic wastewater is one of the environmental problems, which is interesting to study. Domestic wastewater, in addition to causing environmental pollution, can also cause discomfort and even health problems. One way to reduce the impact of domestic wastewater is to treat domestic wastewater before the environment is discharged. This study aims to describe the character of domestic wastewater in Tembalang sub-district, Tembalang district, Semarang city, and the use of activated zeolites and activated zeolites to reduce COD, pH, BOD, and TSS in domestic wastewater. Also, to compare the parameters of wastewater with regulations in force (Minister of Environment and Forestry Regulation No: 68 of 2016). This research is expected to improve the quality of domestic wastewater by adsorption using natural zeolite and activated zeolite adsorbents. The results showed that the adsorption treatment with natural zeolites and activated zeolites significantly improved water quality. The results of adsorption by natural zeolites showed a decrease in COD of 21.8%, a pH of 11.5%, BOD of 9.2%, and a TSS of 10.8%. Whereas adsorption by HCl-activated zeolite resulted in a decrease in COD of 78.9%, pH of 16.2%, BOD of 11.8% & TSS of 74.4%. While H2SO4-activated natural zeolite reduced COD by 85.5%, pH 17.9%, BOD 12.6% and TSS 89.7%.